Picturing Musical Enchantment and Divine Enthusiasm: Some Reading Proposal Through Ancient Greek Vase-Painting (5th-4th Century BC) - Toillon, Valérie (Eikón / Imago, 2017)
The study of ancient Greek vase-painting of 5th and 4th centuries BC shows that emotions, especially what is called “enthusiasm”, enchantment or divine possession, is pictured using bodily movement and sight. Such an affirmation is no novelty. But a more careful study of the corpus, linked to enthusiasm and divine possession's vocabulary shows that the bearings pictured are not just stylistic effects. In fact, those have a meaning, directly connect to ancient Greeks concepts on musical enchantment and divine madness.